2007
DOI: 10.1111/j.1551-2916.2007.01541.x
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Formation of Silicon Carbide Nanofibers on Cordierite Substrates

Abstract: Twenty‐five years of diesel particulate filter (DPF) developments have shown that high‐volume ceramic materials are well suited for the harsh requirements of exhaust after treatment. Nevertheless, problems regarding filter reliability and durability associated with the regeneration of the filter have limited their serious application until only recently. To extend useful filter life, the present study has examined the growth of silicon carbide (SiC) nanofibers by a simple carbothermal reduction process on cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…7(b) shows the growth direction of the nanowire). This observed growth direction is indeed typical of SiC nanowires grown by a solution–precipitation mechanism 24,62,64 . In some cases, the SiC nanowires contained arrays of planar defects, also resulting in characteristic multiple reflexes in the diffraction pattern (see SAED pattern in Fig.…”
Section: Resultsmentioning
confidence: 60%
“…7(b) shows the growth direction of the nanowire). This observed growth direction is indeed typical of SiC nanowires grown by a solution–precipitation mechanism 24,62,64 . In some cases, the SiC nanowires contained arrays of planar defects, also resulting in characteristic multiple reflexes in the diffraction pattern (see SAED pattern in Fig.…”
Section: Resultsmentioning
confidence: 60%
“…In most of the cases, the nanostructures produced on the cell wall surfaces had a length in the range of 2–3 μm . The growth of the nanostructures was by a vapor–liquid–solid (VLS) mechanism in which gaseous precursor molecules first dissolve in a liquid droplet formed by the catalysts at high temperature . The crystallization of nanostructures takes place upon the supersaturation of the catalyst droplet with the precursor molecules.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the use of preceramic polymers is very promising, due to the great tailorability of their structures on a molecular scale and ease of processing. It has been shown that various types of nanostructures, such as whiskers, 2 nanotubes, 3–5 and nanocables 6 /wires 7–9 /fibers 10–12 of different compositions can be produced directly from preceramic polymers, without the use of any transition metal additives as catalyst. Recently, great progress has been made in the production of nanostructures from preceramic polymers (mostly polysilazanes or polycarbosilanes (PCSs)) by applying catalyst‐assisted pyrolysis (CAP), leading to improved yield and the formation of varied morphologies.…”
Section: Introductionmentioning
confidence: 99%